2004
DOI: 10.1074/jbc.m313598200
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stranded Breaks in DNA but Not Oxidative DNA Base Damages Block Transcriptional Elongation by RNA Polymerase II in HeLa Cell Nuclear Extracts

Abstract: Transcription and repair of many DNA helix-distorting lesions such as cyclobutane pyrimidine dimers have been shown to be coupled in cells across phyla from bacteria to humans. The signal for transcription-coupled repair appears to be a stalled transcription complex at the lesion site. To determine whether oxidative DNA lesions can block correctly initiated human RNA polymerase II, we examined the effect of site-specifically introduced oxidative damages on transcription in HeLa cell nuclear extracts. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 59 publications
5
105
0
4
Order By: Relevance
“…8-oxoG, thymine glycol) to block RNA pol II during transcription. Some studies show that RNA pol II can bypass an 8-oxoG lesion (Kathe et al, 2004;Larsen et al, 2004;Tornaletti et al, 2004;Viswanathan and Doetsch, 1998), which is a non-bulky lesion repaired by BER, while some other groups could see a partial stalling of RNA pol II . Sarasin and coworkers have suggested that the repair of 8-oxoG on a transcribed strand results in a competition between BER and TCR components, dependent upon which enzymes arrive first to the lesion (Pastoriza-Gallego et al, 2007).…”
Section: The Role Of Csb In Repair Of Oxidative Dna Damagementioning
confidence: 99%
“…8-oxoG, thymine glycol) to block RNA pol II during transcription. Some studies show that RNA pol II can bypass an 8-oxoG lesion (Kathe et al, 2004;Larsen et al, 2004;Tornaletti et al, 2004;Viswanathan and Doetsch, 1998), which is a non-bulky lesion repaired by BER, while some other groups could see a partial stalling of RNA pol II . Sarasin and coworkers have suggested that the repair of 8-oxoG on a transcribed strand results in a competition between BER and TCR components, dependent upon which enzymes arrive first to the lesion (Pastoriza-Gallego et al, 2007).…”
Section: The Role Of Csb In Repair Of Oxidative Dna Damagementioning
confidence: 99%
“…Therefore a unifying principle for damage-dependent neurodegeneration would be the prediction that deficits in TCR and SSB repair should lead to increased apoptosis of post-mitotic neurons, especially since single strand breaks are also transcription blocking lesions (Kathe et al, 2004). Neurodegeneration might be ascribed to the greater relative importance of a TCR-like repair in differentiated brain cells such that a failure of TCR triggers an apoptotic response (Ljungman and Zhang, 1996;Proietti De Santis et al, 2002;D'Errico et al, 2003).…”
Section: Do the Human Dna Repair Deficient Diseases Delineate Specifimentioning
confidence: 99%
“…A recent suggestion that RNA pol II is a universal sensor of DNA damage (Lindsey-Boltz and Sancar, 2007) blurs the distinction between TCR and global repair. The neurological symptoms of CS patients have been ascribed to defective repair in the brain of endogenous oxidative damage that blocks transcription (Kuraoka et al, 2000;Osterod et al, 2002;de Waard et al, 2003;Kyng et al, 2003;Tuo et al, 2003;Cline et al, 2004), but the more common oxidative base damages (8-oxo-G, 5-hydroxycytosine, thymine glycols) do not block transcription and are therefore not the culprits in neurodegeneration (Kathe et al, 2004). CSA and CSB cells are however different in their responses to oxidative damage, despite overlap in clinical symptoms (de Waard et al, 2004;D'Errico et al, 2007).…”
Section: Do the Human Dna Repair Deficient Diseases Delineate Specifimentioning
confidence: 99%
See 2 more Smart Citations